SSP 2004 Proceedings of the 8th International Conference on Solid State Physics, SSP 2004, Workshop "Mössbauer Spectroscopy of Lacally Heterogeneous Systems", held in Almaty, Kazakhstan, 23-26 August, 2004 - Kadyrzhanov, K.K.; Rusakov, V.S.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2006)
This volume contains papers presented at the 8th International Conference on Solid State Physics (SSP 2004), Workshop "Mössbauer Spectroscopy of Locally Heterogeneous Systems", held in Almaty, Kazakhstan, 23–26 August 2004. It should be of interest to researchers and PhD students working or interested in recent results in the locally inhomogeneous system investigations by Mössbauer Spectroscopy and the new concepts of data evaluation of complex Mössbauer spectra.
The Electronic and Magnetic Properties of FCC Iron Clusters in FCC 4D Metals -- Magnetic Properties of Co and Ni Substituted ?-Fe3N Nanoparticles -- La-Zn Substituted Hexaferrites Prepared by Chemical Method -- Preparation and Properties of Iron and Iron Oxide Nanocrystals in MgO Matrix -- How can Mössbauer Spectrometry Contribute to the Characterization of Nanocrystalline Alloys? -- Nanostructure and Phases Formation under Mechanical Alloying of Bynary Powder Mixtures of Fe and sp-Element (M); M = C,B,Al,Si,Ge,Sn -- Improvements in Depth Selective Electron Mössbauer Spectroscopy -- Thermal Induced Processes in Laminar System of Stainless Steel — Beryllium -- Mössbauer Spectroscopy of Locally Inhomogeneous Systems -- Mössbauer Study of Ferrite-garnets as Matrixes for Disposal of Highly Radioactive Waste Products -- Magnetic Phase Transitions in Nanoclusters and Nanostructures.
Keywords: Solid state physics; Spectroscopy; Microscopy; Solid State Physics; Spectroscopy and Microscopy